Clinical testing of three novel transient receptor potential cation channel subfamily V member 1 antagonists in a pharmacodynamic intradermal capsaicin model. (10th April 2018) - Sjögren, E.; Kullenberg, T.; Jonzon, B.; Segerdahl, M.; Stålberg, O.; Halldin, M.M.; Sundgren‐Andersson, A.K.
Abstract: Background: The transient receptor potential cation channel subfamily V 1 (TRPV1) is involved in nociception and has thus been of interest for drug developers, as a target for novel analgesics. However, several oral TRPV1 antagonists have failed in development, and novel approaches to target TRPV1 with innovative chemistry are needed. Method: This work describes an intradermal microdosing approach in humans for pharmacodynamic deductions and pharmacological profiling of compounds. First, a human capsaicin model was developed, to generate pharmacodynamic translational data (Study Part A, n  = 24). Then, three small molecule TRPV1 antagonists (AZ11760788, AZ12048189 and AZ12099548) were investigated in healthy volunteers (Study Part B, n  = 36), applying the established model. Pain and flare were assessed by Visual Analogue Score and laser Doppler, respectively. Results: The developed model proved useful for pharmacologic deductions; all compounds caused a dose‐dependent inhibition of capsaicin‐induced pain and flare responses, with a rank order potency of AZ11760788 > AZ12048189 ≫ AZ12099548. In addition, the dose–response data showed that the minimal antagonist concentrations needed to inhibit TRPV1 was ≥6–7 times the equilibrium dissociation constant for each compound. Conclusion: With careful design of a pharmacodynamic translational human pain model, it was possible to rank order TRPV1 efficacy among three investigational TRPV1 antagonists, and to estimate human efficacious concentrations. Significance: This fast and cost‐effective translational approach allows for generation of human target engagement information early in drug development. This could be of value for other development programmes where pharmacological targets are expressed in peripheral sensory nerves.